Newfoundland rhapsody : Frederick R. Emerson and the musical culture of the island - Colton, Glenn David, 1968- (McGill-Queen's University Press, 2014)
"Frederick Rennie Emerson (1895-1972) was a dynamic presence in the cultural and intellectual life of Newfoundland and Labrador for much of the twentieth century. A musician, lawyer, educator, and folklore enthusiast, Emerson was a central figure in the preservation and mediation of Newfoundland culture in the tumultuous decades prior to and following Confederation with Canada in 1949